Advances in phototherapy for psoriasis and atopic dermatitis. (2nd November 2019) - Kemény, Lajos; Varga, Emese; Novak, Zoltan
ABSTRACT: Introduction : Phototherapy has long been used for the treatment of inflammatory skin diseases, such as psoriasis and atopic dermatitis. The most frequent treatment approach utilizes ultraviolet (UV) light, however, recently, different lasers and low-level light therapies (LLLT) emitting wavelengths in the spectrum of the visible light have also been tried for the treatment of inflammatory skin diseases with variable success. Areas covered : This review provides an update on the different forms of phototherapy used for the treatment of psoriasis and atopic dermatitis. The proposed mechanism of action of the different phototherapeutical approaches are covered, including the immunosuppressive effect of UV light, the anti-inflammatory effect of vascular lasers and the LLLT induced photobiomodulation. The clinical efficacy of the different treatment options is also discussed. Expert opinion : Based on the efficacy and safety, NB-UVB represents the gold standard for treating psoriasis and atopic dermatitis. The UVB excimer laser and excimer lamp might be the best option for clearing localized therapy-resistant lesions. Home UV phototherapy systems might promote treatment adherence and better compliance of the patients. Vascular lasers, IPLs and LLLT, however, can not currently be recommended for the treatment of inflammatory skin diseases because of the lack of well-controlled studies.